2020
DOI: 10.47892/rgp.2020.401.1023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tolerance and acceptability between mannitol solution and polyethylene glycol as bowel preparation for colonoscopy: a three-center study

Abstract: Introduction: Adequate bowel preparation is one of the most important factors related to the yield of colonoscopy. Low-quality bowel preparation has been associated with lower adenoma detection rates and increased healthcare expenses. Bowel preparation is a major impediment to undergo colonoscopy since it is perceived as an unpleasant experience by patients. Objective: This study was aimed to assess tolerance and acceptability of the bowel preparation using either polyethylene glycol (PEG) or mannitol solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition, addressing existing barriers such as the discomfort produced by bowel preparation could itself facilitate individuals' participation; studies show that CRC screening participants have a preference for non-laxative [60] and low-volume [118] preparations. In fact, some of the included studies have investigated alternatives to the commonly used standard preparation PEG-ELS 4L, such as Sodium Phosphate (NaP) tablets [126], Mannitol solutions [127] and low-volume preparations such as Moviprep ® AscPEG-2L (PEG combined with ascorbic acid) and CitraFleet ® PiMg (sodium picosulfate combined with magnesium citrate) [118]. NaP tablets, for example, were preferred over the PEG solution by 66% of the 53 participants interviewed by Gurudu et al [126].…”
Section: Potential Addressing Measures For Increasing Participation With Visual Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, addressing existing barriers such as the discomfort produced by bowel preparation could itself facilitate individuals' participation; studies show that CRC screening participants have a preference for non-laxative [60] and low-volume [118] preparations. In fact, some of the included studies have investigated alternatives to the commonly used standard preparation PEG-ELS 4L, such as Sodium Phosphate (NaP) tablets [126], Mannitol solutions [127] and low-volume preparations such as Moviprep ® AscPEG-2L (PEG combined with ascorbic acid) and CitraFleet ® PiMg (sodium picosulfate combined with magnesium citrate) [118]. NaP tablets, for example, were preferred over the PEG solution by 66% of the 53 participants interviewed by Gurudu et al [126].…”
Section: Potential Addressing Measures For Increasing Participation With Visual Testsmentioning
confidence: 99%
“…NaP tablets, for example, were preferred over the PEG solution by 66% of the 53 participants interviewed by Gurudu et al [126]. In the study performed by Piñerúa-Gonsálvez et al [127], the PEG solution was also less chosen to be used again in future colonoscopies compared to the mannitol solution (71.4% of the individuals in the PEG group vs. 82.9% of the individuals in the mannitol group). Finally, Rodriíguez de Miguel et al [118] who, studied PEG-ELS 4L-related adverse effects compared to the low volume preparations on a cohort of 292 individuals, found that participants using PEG-ELS 4L required antiemetics more often compared to the AscPEG-2L and PiMg groups (22.4% vs. 2.1% and 8.2%, respectively; p < 0.0001).…”
Section: Potential Addressing Measures For Increasing Participation With Visual Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…If necessary, cleaning enema is added. The bowel cleaning effect is not good, and the preparation time is long [ 4 ]. Traditional bowel preparation requires a long time for patients' preoperative diet control, and high-pressure enema may cause adverse reactions such as bowel edema and ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, general safety and tolerability were comparable between mannitol and PEG formulations. All published studies used doses of mannitol of between 50 and 150 g, given in a single dose, except for one study which tested a split dose of mannitol solution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%